Comparison of dobutamine-stress magnetic resonance imaging and dipyridamole-Tl-201-SPECT as alternative strategies for the detection of coronary artery disease in patients not suitable for stress-echocardiography - Schmidt, M.; Jochims, M.; Theissen, P.; Baer, F. M.; Crnac, J.; Voth, E.; Schneider, C. A.; Erdmann, E.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2001)
Aim: During the past decade stress-echocardiography has gained increasing popularity for detection of myocardial ischemia in patients with coronary artery disease. However, about 10% to 15% of the patients submitted for stress-echocardiography do not have an adequate acoustic window. The purpose of this study was to compare high-dose dobutamine-stress magnetic resonance imaging (dobutami-ne-MRI) with dipyridamole-Tl-201-SPECT (dipyridamole-SPECT) as alternative strategies for detection of myocardial ischemia in patients with inadequate image quality by stress-echocardiography. Patients and Methods: Of 296 patients which were consecutively submitted to stress-echocardiography 45 patients (15%) had two or more segments that could not be evaluated according to the 16-seg-ment-model of the American Society of Echocardiography. They underwent dobutamine-MRI and dipyridamole-SPECT studies, which were evaluated using a 28-segment modeli. Myocardial segments were attributed to perfusion territories of the coronary arteries. The results of ischemia detection were compared to the results of coronary angiography (stenosis >50%.) Results: In comparison to coronary angiography dobutamine-MRI yielded a sensitivity of 87%, a specificity of 86%, a positive predictive value of 93%, a negative predictive value of 75% and a diagnostic accuracy of 86%. Eor dipyridamole-SPECT results were 90%, 86%, 93%, 80% and 89%, respectively. These values were not significantly different. Conclusions: In patients not suitable for stress-echocardiography, both dobutamine-MRI and dipyridamole-SPECT are reliable strategies for detection of myocardial ischemia. Selection is dependent on the patient criteria, technical considerations, local logistics and experience of the observer.
Keywords: Coronary artery disease; stress-echocardiography; magnetic resonance imaging; myocardial scintigraphy; T1-201 -SPECT; pharmacological stress testing